The impact of electrolytic pH on photoelectrochemical water oxidation. Issue 7 (1st February 2023) - Biswas, Neeraj Kumar; Srivastav, Anupam; Saxena, Sakshi; Verma, Anuradha; Dutta, Runjhun; Srivastava, Manju; Upadhyay, Sumant; Satsangi, Vibha Rani; Shrivastav, Rohit; Dass, Sahab
Abstract : Harnessing solar energy for clean and sustainable fuel production by photoelectrochemical water oxidation over different timescales has been extensively investigated. Abstract : Harnessing solar energy for clean and sustainable fuel production by photoelectrochemical water oxidation over different timescales has been extensively investigated. However, the light-driven photoelectrochemical water oxidation reaction for artificial photosynthesis suffers from poor photon-to-current efficiency. Herein, we demonstrate an experimental analysis of electrolytic pH on photoelectrochemical syngas production by varying the pH of the KOH and NaOH electrolytes using the N–ZnO photoelectrode and analyzing all variables. A maximum photocurrent of 13.80 mA cm −2 at 1.23 V vs. RHE with a 43.51% photon-to-current conversion efficiency was obtained at pH 13 in the aqueous NaOH electrolyte.